Hoppa på! - Aspelin, Johan; Grandell, Chotta; Granvik, Nina; Hukkinen, Nina; Nylund, Emilia; Nylund, Niklas, 1964-; Raita, Matti; Thibblin, Joachim ([Helsingfors] : Folkhälsan, 2014)
2 versiota kappaleesta Hoppa på!
Julkaisussa teksti: Promotion not for sale.
Esityksessä mukana: Matti Raita, Joachim Thibblin, Johan Aspelin, Nina Hukkinen, Chotta Grandell, Nina Granvik, Emilia Nylund, Niklas Nylund.
Keywords: lastenlaulut